Government Capacity of Regional Government of South Solok Regency in Reducing Stunting - Fitri, Yulia; Yusran, Rahmadani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This study analyzes government capacity or the ability of local governments to reduce stunting in South Solok Regency using descriptive qualitative methods. This research was conducted in the Regional Government of South Solok Regency. For informants who were selected purposively by obtaining from government capacity the local government has not been optimally implemented, this is because there are problems faced by the Regional Government, namely the special APBD budget for handling stunting does not exist, the special budget for stunting comes from the central budget and the implementation budget is limited, not optimal coordinating between OPDs, in carrying out holistic and integrative education programs the Education Office is carrying out activities going well. The problem faced is that the understanding of PAUD teachers is sometimes not conveyed to children in the field, so the training is not carried out in accordance with applicable policies, and the cadres at the Posyandu do not receive Posyandu cadre training.